The Good News From Pakistan - Barber, Michael (Reform, 2013)
Keywords: ⛔ No DOI found

How the world’s most improved school systems keep getting better - Mourshed, Mona; Barber, Michael; Chijioke, Chinezi (McKinsey & Company, 2010)

Deliverology 101: A Field Guide For Educational Leaders - Barber, Michael; Moffit, Andy; Kihn, Paul (Corwin Press, 2011)
'Michael Barber's pioneering work as head of my Delivery Unit helped ensure real progress, not just with our education reforms, but with healthcare and policing too. It attracted worldwide attention. This guide distils the wisdom he gained at that time and has refined since. I strongly recommend it.' - Tony Blair, Former UK Prime Minister 1997-2007A step-by-step approach to delivering resultsMichael Barber, former chief advisor on delivery to British Prime Minister Tony Blair, and his colleagues Andy Moffit and Paul Kihn thoroughly describe Barber's proven reform delivery processes in this practical field guide. The timing is ideal, as Barack Obama's administration prioritizes education reform. Citing education reform case studies from more than 20 countries, the authors assert that most previous reforms were unsuccessful due to failed implementation. This book focuses on how to accomplish meaningful results, including:- Significant and ongoing education reform- Excellence and equity across public educationThe authors illustrate a field-tested program that ensures reform is achieved in the most profound sense, with students able to see, feel, and reap the benefits of a high-quality education. It is based not only on the experience of the Blair administration but also on case studies of successful implementation of reform in the U.S. and elsewhere.Listen as Barber describes the importance of the book:
Keywords: Education / Decision-Making & Problem Solving; Education / Leadership